A Common Glaucoma-risk Variant of SIX6 Alters Retinal Nerve Fiber Layer and Optic Disc Measures in a European Population: The EPIC-Norfolk Eye Study. Issue 9 (September 2018) - Khawaja, Anthony P.; Chan, Michelle P.Y.; Yip, Jennifer L.Y.; Broadway, David C.; Garway-Heath, David F.; Viswanathan, Ananth C.; Luben, Robert; Hayat, Shabina; Hauser, Michael A.; Wareham, Nicholas J.; Khaw, Kay-Tee; Fortune, Brad; et al.
Abstract : Purpose: A common missense variant in the SIX6 gene (rs33912345) is strongly associated with primary open-angle glaucoma (POAG). We aimed to examine the association of rs33912345 with optic disc and retinal nerve fiber layer (RNFL) measures in a European population. Methods: We examined participants of the population-based EPIC-Norfolk Eye Study. Participants underwent confocal laser scanning tomography (Heidelberg Retina Tomograph II, HRT) to estimate optic disc rim area and vertical cup-disc ratio (VCDR). Scanning laser polarimetry (GDxVCC) was used to estimate average RNFL thickness. The mean of right and left eye values was considered for each participant. Genotyping was performed using the Affymetrix UK Biobank Axiom Array. Multivariable linear regression with the optic nerve head parameter as outcome variable and dosage of rs33912345 genotype as primary explanatory variable was used, adjusted for age, sex, disc area, axial length, and intraocular pressure. We further repeated analyses stratified into age tertiles. Results: In total, 5433 participants with HRT data and 3699 participants with GDxVCC data were included. Each "C" allele of rs33912345 was associated with a smaller rim area (−0.030 mm 2 [95% CI −0.040, −0.020]; P =5.4×10 −9 ), a larger VCDR (0.025 [95% CI 0.017, 0.033]; P =3.3×10 −10 ) and a thinner RNFL (−0.39 μm [95% CI -0.62, -0.15]; P =0.001). The RNFL association was strongest in the oldest age tertile, whereas rim area and VCDR associations were strongest in the youngest and oldest age tertiles. Conclusions: The protein-coding SIX6 variant rs33912345, previously associated with POAG, has a functional effect on glaucoma-associated optic nerve head traits in Europeans. Abstract : Supplemental Digital Content is available in the text.